Răspuns :
[tex]x {( - x + 1)}^{3} - x {( - x + 1)}^{2} - x(x - 1)[/tex]
[tex] = x{[ - (x - 1)]}^{3} - x{[ - (x - 1)]}^{2} - x(x - 1)[/tex]
[tex] = x \times {( - 1)}^{3} \times {(x - 1)}^{3} - x \times {( - 1)}^{2} \times {(x - 1)}^{2} - x(x - 1)[/tex]
[tex] = x \times ( - 1) \times {(x - 1)}^{3} - x \times 1 \times {(x - 1)}^{2} - x(x - 1)[/tex]
[tex] = - x {(x - 1)}^{3} - x {(x - 1)}^{2} - x(x - 1)[/tex]
[tex] = -x(x - 1)[ {(x - 1)}^{2} + (x - 1) +1][/tex]
[tex] = -x(x - 1)[{x}^{2} - 2x + 1+x-1 +1] [/tex]
[tex]= -x(x + 1)( {x}^{2} - x+1) [/tex]
[tex] = x{[ - (x - 1)]}^{3} - x{[ - (x - 1)]}^{2} - x(x - 1)[/tex]
[tex] = x \times {( - 1)}^{3} \times {(x - 1)}^{3} - x \times {( - 1)}^{2} \times {(x - 1)}^{2} - x(x - 1)[/tex]
[tex] = x \times ( - 1) \times {(x - 1)}^{3} - x \times 1 \times {(x - 1)}^{2} - x(x - 1)[/tex]
[tex] = - x {(x - 1)}^{3} - x {(x - 1)}^{2} - x(x - 1)[/tex]
[tex] = -x(x - 1)[ {(x - 1)}^{2} + (x - 1) +1][/tex]
[tex] = -x(x - 1)[{x}^{2} - 2x + 1+x-1 +1] [/tex]
[tex]= -x(x + 1)( {x}^{2} - x+1) [/tex]